POLITICS OF IDENTITY ON GREAT 212’S REUNION - Ida Susilowati; Nur Rohim Yunus; Muhammad Sholeh (UNIDA Gontor, 2019)
Action 212 and Great 212's reunion were often discussed as a phenomenon of Muslims in Indonesia nowadays. Various labeling arose from Islamic identity politics in Indonesia, the rise of Muslims in Indonesia, even the manifestation of transnationalism in global politics. This paper aims to understand the real phenomenon of the emergence of action 212 that are not static, and continue to take a role in political government in Indonesia which is considered less than optimal in implementing rule of law in legal law in Indonesia. Pancasila democracy was the main foundation in assessing the reunion action that was held several months ago, so that there was relevance between the Grand Reunion movement 212 and the Pancasila ideology as the fundamental basis of Indonesia.